Applying Augmented Reality Technology to Build Serious Games in STEM Education - Anh, Ngo Thi Phuong; Huong, Nguyen Lan; Hung, Nguyen Quoc; Hai, Tuong Duy; Khuyen, Nguyen Thi To (International Journal of STEM Education for Sustainability, 2025)
Serious games are increasingly recognized as an innovative pedagogical tool in STEM education, thanks to their ability to create engaging, interactive and competency-based learning environments, thereby improving student learning outcomes. In this context, Augmented Reality (AR) technology has emerged as a breakthrough in science and technology, allowing learners to interact directly with vivid 3D models in real space, thereby strongly promoting the ability to explore and learn by experience. Integrating learning games (Serious games) with AR technology in teaching science subjects not only brings a new learning experience, but also opens up a promising approach to developing creative thinking, problem-solving skills and systematic thinking in learners. This study aimed to: (1) design AR-enhanced serious games aligned with the EDP framework using the CoSpaces Edu platform; and (2) evaluate their impact on students’ engagement, perceptions of STEM, and development of engineering design skills. The mixed-method research design used in this study. In this study, we applied the CoSpaces Edu platform to design and deploy twelve AR-integrated learning games, corresponding to key topics in the Natural Science and Physics curriculum at middle and high school levels. The games were built to integrate academic content with virtual interactive experiences, thereby exploiting the potential of AR technology in improving the quality of science teaching in the direction of STEM education.